Educación universitaria y emprendimiento empresarial en los estudiantes de contabilidad de la Universidad Nacional de la Amazonía Peruana periodo 2024 - Barria Torres, Renzo Luis (2024)
The objective of this research was to determine the relationship between the university education provided to Accounting students at the National University of the Peruvian Amazon and the level of business entrepreneurship developed during the period 2024, with a type of quantitative research, with a non experimental design. and type of transectional or transversal design, I included as a population 260 students belonging to the Accounting career of the National University of the Peruvian Amazon, concluding that a moderately strong positive correlation is established (0.614, p < 0.01) between education university taught to Accounting students at the National University of the Peruvian Amazon and the level of business entrepreneurship developed during the period 2024. This suggests that as the level of university education increases, the level of business entrepreneurship activity also tends to increase. , in addition to The moderately strong positive correlation (0.543, p < 0.01) between teacher training and attitudes towards entrepreneurship indicates an association between both aspects. Accounting students at the National University of the Peruvian Amazon who receive greater teaching training tend to have more favorable attitudes toward entrepreneurship. This association highlights the importance of educational support and encouragement provided by the university in the entrepreneurial intention of students.